Cognitive Activity and Creativity of Junior Schoolchildren with the High Intellectual Abilities in the Different Educational Environment - Shumakova N.B (Moscow State University of Psychology and Education, 2019)
Article is devoted to a study of cognitive activity and creativity of junior schoolchildren with the high intellectual abilities. The paper presents the results of an empirical study of the special features of cognitive activity and creativity of junior schoolchildren with the high intellectual abilities, who are trained in the different educational environment (standard and innovation, enrichment). The hypothesis tested was that the intensity, cognitive level (depth) and latitude of the manifestation of the cognitive activity of the intellectually gifted junior schoolchildren were connected with such parameters of educational environment as cognitive complexity, classroom interaction, and the value of the creative activity of child. In a study participated the intellectually gifted junior schoolchildren of the 2nd and 4th classes (n=101). It was shown that the educational environment has an effect on the manifestations of cognitive activity and verbal creativity of the intellectually gifted junior schoolchildren. The intellectually gifted junior schoolchildren, who are trained in the educational environment, which is characterized by the high level of cognitive complexity, classroom interaction and values of the creative activity of child, reveal the reliably higher indices of verbal creativity, and also level, depth and latitude of cognitive activity, than their gifted peers, who are trained under the standard (traditional) educational environment.